Pengaruh Model Pembelajaran POE terhadap Sikap Ilmiah dan Keterampilan Proses Sains Siswa Kelas XI MA Negeri 1 Samarinda - Oktavia Nuraisa; Sri Purwati; Masitah Masitah; Jailani Jailani; Zenia Lutfi Kurniawati (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The average biology learning outcomes of eleventh-grade students at MA Negeri 1 Samarinda are still below the Minimum Completion Criteria (KKM), while innovative learning models such as POE (Predict-Observe-Explain) have never been implemented. Biology learning has been mostly based on lectures, discussions, assignments, and practicums, while scientific attitude assessments are only taken from daily life and practicum activities. This condition requires the implementation of a model that can actively involve students to encourage scientific attitudes and science process skills (SPS). This study aims to determine the effect of the POE model on the scientific attitudes and SPS of eleventh-grade students on the sensory system material. The method used is a quasi-experimental design with a Nonequivalent Control Group Design, involving class XI-F as the experiment and XI-D as the control. The research instruments are scientific attitude questionnaires and SPS tests. The results of the analysis show significant differences between the experimental and control classes in scientific attitudes (p < 0.05) and SPS (p < 0.05 with the Mann Whitney U test). Improvements in scientific attitudes were demonstrated by an N-gain of 0.35 (moderate) in the experimental class and 0.19 (low) in the control class. Meanwhile, the N-gain of the Student-Based Learning (KPS) reached 0.60 (moderate) in the experimental class and 0.29 (low) in the control class. The conclusion of this study is that the POE model effectively improves the scientific attitudes and science process skills of eleventh-grade students at MA Negeri 1 Samarinda.